Byzantium Between the Ottomans and the Latins : Politics and Society in the Late Empire - Necipoglu, Nevra (Cambridge University Press, 2013)
This book is a study of the political attitudes that emerged among different segments of Byzantine society in response to the Ottoman expansion. Its principal aims are, first, to categorize these attitudes with regard to specific groupings among the urban and rural populations of the Byzantine Empire (e.g. the aristocracy, merchants, lower classes, ecclesiastical and monastic circles) and, secondly, to explore the underlying social and economic factors, besides the more apparent political and religious ones, that played a role in the formation of political attitudes. In an atmosphere of extreme political and military instability marked by a number of civil wars and foreign invasions during the fourteenth and fifteenth centuries, people from different segments of Byzantine society in different regions of the empire sought by various means to secure their best interests in the face of the rapidly expanding Ottoman Empire.